Mengapa menulis skripsi sulit? - Lestari, Ferina Aulia; Wijayati, Primardiana Hermilia (2021)
One of the most important competence in this digitalization era is critical thinking that can be seen in undergraduate thesis writing. But, the process of writing emerge some problems that hinder the critical thinking competence of the students. This qualitative method research aims to describe the difficulties and problems that are faced by students during the undergraduate thesis writing. Questionnaire and interview guideline are the instrument to collect the data. Result revealed that the students have problems in expressing arguments for the importance of research and connecting data with theory in the discussion chapter. They also faced the difficulties in finding reference and the using of correct language aspect, such as punctuation, orthography, variations in diction and expressions, main ideas in one paragraph, cohesion and coherence between paragraphs, as well as a scientific style of writing. The cause is a lack of reading habits and practice critical thinking.